Dyspnea on exertion is an independent predictor of mortality in patients with no baseline cardiovascular or respiratory disorders. (25th November 2020) - Poosala, A; Sydo, N; Allison, T.G
Abstract: Background: Dyspnea on exertion (DOE) is defined as a subjective experience of breathing discomfort that consists of qualitatively distinct sensations (Effort/work of breathing, Chest tightness, Air hunger) that vary in intensity elicited by physical activity. Although DOE is a common presenting symptom in patients pertaining to cardiovascular and respiratory disorders, its prognostic importance in patients with no prior cardiovascular (CV) or respiratory disorders is unclear. Purpose: The purpose of this study is to determine the prognostic significance of dyspnea on exertion (DOE) in patients with no prior diagnosis of CV or respiratory disorders. Methods: We reviewed the Mayo Integrated Stress Center database for the period September 1993 through November 2010. Residents of Minnesota with no known heart disorders and no known history of COPD or other respiratory disorders were included in the study. Patients with abnormal ECG findings were excluded to rule out possible undiagnosed CV disorders. Limiting symptoms of DOE with reduced exercise capacity (FAC<90%). Our primary outcome was mortality which was adjusted for age, sex, smoking history, diabetes, hypertension, obesity, negative chronotropic medications. Statistical analysis was performed to evaluate hazard ratio using Cox regression models in SAS Studio. Results: A total of 101, 455 exercise tests were reviewed to identify 18960 patients (female = 6755, 35.6%) who met the study criteria. Mean age at the time of referral was 51.2±10 years (mean ± SD) and mean follow-up was 12±10 years (mean ± SD). There were 1331 (7%) deaths from all causes, out of which 368 (27.6%) deaths are from DOE patients, and there were 428 (2.2%) deaths from cardiac causes, out of which 141 (32.9%) deaths are from DOE patients. We found that DOE was an independent predictor of mortality from all causes with hazard ratio [95% CI] = 1.690 [1.488–1.918], p≤0.0001, and from cardiac causes with hazard ratio [95% CI] = 1.997 [1.613–2.473], p≤0.0001. Product-limit survival estimates of patients with and without DOE are shown in Figure 1. Conclusion: Based on our study findings, we conclude that dyspnea on exertion is an independent predictor of mortality in patients with no baseline CV or respiratory disorders. Patients presenting with dyspnea alone as a presenting compliant should be evaluated thoroughly and treated accordingly to reduce the associated mortality outcomes. Funding Acknowledgement: Type of funding source: None